Methodologies to assess community-based animal health workers curricula and training programs: a mini review - Matos, Alice; Hoet, Armando E.; Bessler, Andrea L.; Berrian, Amanda M. (Frontiers in Veterinary Science, 2026)
IntroductionWell-trained and supervised community-based animal health workers (CAHW) are key contributors to the veterinary workforce with significant potential to increase access to veterinary care for underserved communities. Recognizing their value, the World Organisation for Animal Health (WOAH) recently published the Competency and Curriculum Guidelines for CAHWs to help harmonize their training within and across countries. This recent advancement must be accompanied by a methodology for curriculum and training assessment to determine whether existing CAHW training programs meet the established recommendations.MethodsUsing PRISMA guidelines, a literature review was conducted to explore the current assessment practices in CAHW training programs, aiming at guiding the development of a curriculum assessment tool. The articles were thoroughly reviewed, and relevant information was extracted and analyzed using the Kirkpatrick Model for training evaluation and the competency-based education (CBE) framework.ResultsOf the 203 publications screened, seven met the selection criteria and were included in the review. Most of the authors utilized multiple methods such as interviews, surveys, and direct observation to assess different training effectiveness levels (reaction, learning, behavior, and/or results) and competency types (knowledge, skills, and/or abilities). Conversational methods of assessment were preferred, and both learners (CAHWs) and their clients (i.e., livestock owners) were frequently engaged in the process.ConclusionThis review highlights the need to develop and implement standardized curriculum and training assessments to complement the recent WOAH guidelines and, ultimately, advance CAHWs’ proficiency and animal healthcare delivery.